Implementation of Local Regulation No. 3 of 2015 About Non-Smoking Area at Kamonji Community Health Centers, Palu Barat District, Palu - Herman; Mohammad Fikri; Sadli Syam (International Journal of Health, Economics, and Social Sciences (IJHESS), 2021)
Smokers 2-4-fold risk of developing infectious disease. Creating a non-smoking area is one of the ways to protect the societies from the negative effect of cigarette smoke and to reduce number of active smokers. The existence of local regulations no. 3 of 2015 about non-smoking area in Palu applied by Kamonji Community Health Centers is one of the ways to overcome the smoking behavior. In the first quarter, there were 20 cases of violations and decreased in the second quarter to four to 16 cases and rose to 19 cases in the fifth quarter. This research aims at finding out the implementation and the behavior goals related to the smoking behavior at Kamonji Community Health Centers. This was qualitative research with a case study approach. The result show that the implementation variables that was conducted, consisted of communication, resources, disposition, and the structure of organization were not optimally applied. 10 out of 15 informants do not know about the local regulations. It means that the delivery of information to the policy goals did not improve the public knowledge that have an impact on the society’s compliance levels to the policy. In conclusions, the implementation of local regulation no. 3 of 2015 about non-smoking area at Kamonji Community Health Centers was not optimally applied. It is expected that related agencies can improve the process of information dissemination and monitoring of non-smoking area in Palu, especially in Kamonji Community Health Centers.